Nutritional status of U.S. elite heptathletes - 1999 USA track and field development project - Houtkooper, L. B.; Mullins, V. A.; Taylor, A.; Poole, C. (1999)
The purposes of this study were to continue and to expand the nutritional assessment program of the elite U.S. Heptathlete Development Project. The objectives of this study were to: · provide assistance to these athletes for development of the dietary component of their training and competition programs in order to improve or maintain desirable nutritional status. · conduct initial and/or one year follow-up assessments of selected dietary, clinical, and biochemical components of the nutritional status of elite U.S. heptathletes during training and competition.